Analysis of Factors that Influence Mandatory Annual Report Disclosures at The IDX Mining Company - Mimelientesa Irman; Lisa Fitrianis (Journal of Management and Bussines (JOMB), 2019)
This research aims to examine the influence of company size, company age, ownership structure and profitability on mandatory disclosures of mining company annual reports. The population in this research were all mining companies listed on the Indonesia Stock Exchange in 2013-2017, which were 41 companies. Sample selection was done by purposive sampling method and 14 selected companies were selected. The data used in this research was secondary data by collecting company annual reports from the Indonesia Stock Exchange website, www.idx.co.id. While the analytical method used are classical assumption and hypothesis testing and regression analysis. The results of this study show that the variable company size, company age, and profitability had an influence to mandatory disclosure of annual reports, while the ownership structure had not influence to mandatory disclosure of annual reports. All of independent variable in this research had an influence to mandatory disclosure of annual reports. Keyword : Company Size, Company Age, Ownership Structure, Profitability and Mandatory Disclosure.